Menstrual dignity and menstrual experiences among riverside adolescents in the Brazilian Amazon: participatory development of an educational technology using Paulo Freire’s research itinerary - Amanda Guimarães Cunha; Marta Lenise do Prado; Elizabeth Teixeira; Cláudio Claudino da Silva Filho; Mary Elizabeth de Santana; Rubenilson Caldas Valois; George Pinheiro Carvalho; Lucrecia Aline Cabral Formigosa; Haroldo Gonçalves de Jesus; Reinaldo de Souza Guimarães; Gisele Maria Cardoso da Silva; Marinara de Nazaré Araújo Lobato; et al. (PLoS ONE, 2026)
Objective To understand menstrual experiences and perceptions of menstrual dignity among riverside adolescent girls in the Brazilian Amazon in order to support the participatory co-creation of an educational technology using Paulo Freire’s research itinerary. Methods Technology development research, with a qualitative approach and participatory interface, grounded in Paulo Freire’s research itinerary, composed of three stages: thematic investigation, coding/decoding and critical unveiling. The study was conducted in a public school located on Caratateua Island, Pará, Brazil, with the participation of 10 adolescents, and the investigation was operationalized through Culture Circles. Data were collected through audio recordings and field diary notes and analyzed using inductive thematic analysis aligned with Freirean stages, and the findings supported the participatory co-creation of an educational technology in the format of a comic book. Results Three main thematic categories emerged: (1) menstruation as emotional and daily life disruption, (2) silence and limited dialogue about menstrual experiences, and (3) sociocultural beliefs influencing menstrual care practices. These findings informed the development of a culturally contextualized comic book addressing menstrual knowledge, self-care, and menstrual dignity. Conclusion The findings highlight the importance of culturally grounded educational approaches for menstrual health. The participatory co-creation process enabled the development of an educational resource aligned with adolescents’ lived experiences and may support future health education strategies and research in menstrual health promotion.